2020
DOI: 10.3390/app10113693
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Element Analysis of the Strength Anisotropy of Fiber-Reinforced Sands Subjected to Direct Shear Load

Abstract: Soil reinforcement with natural or synthetic fibers enhances its mechanical behavior in various applications. Fiber-reinforced sands (FRS) can be relatively anisotropic because of the fiber self-weight and the compaction technique. However, the microscopic mechanisms underlying the anisotropy are still poorly understood. This study used a discrete element approach to analyze the microscopic mechanisms underlying the strength anisotropy of FRS due to fiber orientation. Analysis of contact networks revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous studies reported the implementation of DEM in examining soil-crop, soil-residue, or soil-seed interactions along with the interface of different implements [49,63,65,[71][72][73][74][75]. For example, Zeng et al [65] simulated the emergence dynamics of soybean seedlings through the soil and quantified cotyledon-soil dynamic characteristics including soil resistance, number of the contact points between soil particles and cotyledon, and soil kinetic energy.…”
Section: Applications Of Dem In Soil-plant-machine Interaction Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported the implementation of DEM in examining soil-crop, soil-residue, or soil-seed interactions along with the interface of different implements [49,63,65,[71][72][73][74][75]. For example, Zeng et al [65] simulated the emergence dynamics of soybean seedlings through the soil and quantified cotyledon-soil dynamic characteristics including soil resistance, number of the contact points between soil particles and cotyledon, and soil kinetic energy.…”
Section: Applications Of Dem In Soil-plant-machine Interaction Studiesmentioning
confidence: 99%
“…It is observed from the literature review that most of the previous studies either directly adapted published values or relied on calibration in determining model parameters. In some instances, the model parameters have been selected from the literature based merely on whether the experimental conditions fit into their work [71,74,75,97,110]. As a result, simulation accuracy varied between the referred and proposed studies [96,101].…”
Section: Future Challengesmentioning
confidence: 99%
“…Anisotropic mechanical behaviours of jointed rock mass are key influencers for the deformation and failure of rock engineering, and have been paid attention in recent years [36][37][38][39][40]. RDFN models with different rotation angles and the same size were established to evaluate the anisotropy of rough-jointed rock mass under biaxial compression.…”
Section: Numerical Analysis Of the Anisotropic Mechanical Propertiesmentioning
confidence: 99%
“…Ibraim et al [19] investigated the evolution of pore ratio distribution, rearrangement of soil particles, and dynamic change of stresses in ber-reinforced soils during compaction by DEM. Gong et al [15] used DEM to simulate the microscopic mechanism of strength anisotropy of ber-reinforced sand in direct shear tests. Yang et al [50] studied the in uence of different ber orientations on the contact force distribution between ber and sand particles.…”
Section: Introductionmentioning
confidence: 99%